DNA crosslinking and recombination‐activating genes 1/2 (RAG1/2) are required for oncogenic splicing in acute lymphoblastic leukemia. Issue 11 (26th October 2021) - Zhang, Hao; Cheng, Nuo; Li, Zhihui; Bai, Ling; Fang, Chengli; Li, Yuwen; Zhang, Weina; Dong, Xue; Jiang, Minghao; Liang, Yang; Zhang, Sujiang; Mi, Jianqing; et al.
Abstract: Background: Abnormal alternative splicing is frequently associated with carcinogenesis. In B‐cell acute lymphoblastic leukemia (B‐ALL), double homeobox 4 fused with immunoglobulin heavy chain (DUX4/IGH) can lead to the aberrant production of E‐26 transformation‐specific family related gene abnormal transcript (ERGalt ) and other splicing variants. However, the molecular mechanism underpinning this process remains elusive. Here, we aimed to know how DUX4/IGH triggers abnormal splicing in leukemia. Methods: The differential intron retention analysis was conducted to identify novel DUX4/IGH‐driven splicing in B‐ALL patients. X‐ray crystallography, small angle X‐ray scattering (SAXS), and analytical ultracentrifugation were used to investigate how DUX4/IGH recognize double DUX4 responsive element (DRE)‐DRE sites. The ERGalt biogenesis and B‐cell differentiation assays were performed to characterize the DUX4/IGH crosslinking activity. To check whether recombination‐activating gene 1/2 (RAG1/2) was required for DUX4/IGH‐driven splicing, the proximity ligation assay, co‐immunoprecipitation, mammalian two hybrid characterizations, in vitro RAG1/2 cleavage, and shRNA knock‐down assays were performed. Results: We reported previously unrecognized intron retention events in C‐type lectin domain family 12, member A abnormal transcript (CLEC12Aalt ) and chromosome 6 open reading frame 89 abnormal transcript (C6orf89alt ), where also harbored repetitive DRE‐DRE sites. Supportively, X‐ray crystallography and SAXS characterization revealed that DUX4 homeobox domain (HD)1‐HD2 might dimerize into a dumbbell‐shape trans configuration to crosslink two adjacent DRE sites. Impaired DUX4/IGH‐mediated crosslinking abolishes ERGalt, CLEC12Aalt, and C6orf89alt biogenesis, resulting in marked alleviation of its inhibitory effect on B‐cell differentiation. Furthermore, we also observed a rare RAG1/2‐mediated recombination signal sequence‐like DNA edition in DUX4/IGH target genes. Supportively, shRNA knock‐down of RAG1/2 in leukemic Reh cells consistently impaired the biogenesis of ERGalt, CLEC12Aalt, and C6orf89alt . Conclusions: All these results suggest that DUX4/IGH‐driven DNA crosslinking is required for RAG1/2 recruitment onto the double tandem DRE‐DRE sites, catalyzing V(D)J‐like recombination and oncogenic splicing in acute lymphoblastic leukemia.